PENGARUH VERBAL BULLYING TERHADAP KECERDASAN INTERPERSONAL PADA SISWA SD INPRES KARUWISI 1 KOTA MAKASSAR - Ashar; M. Yusran Rahmat; Nur Al Muqni Hasmaliah Malik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to find out the magnitude of verbal bullying against interpersonal intelligence of SD Inpres Karuwisi 1 Makassar students. This research is quantitative research with an ex post facto approach. Sampling is done using non probability sampling techniques. Data collection techniques through observations, questionnaires, documentation. The population of this study is from the fourth grade of 18 students, whereas for data analysis techniques using the t test. To find out whether or not his verbal influence bullying on interpersonal intelligence students in SD Inpres Karuwisi 1 Makassar. Based on Sig significance (2-tailed) there are 0,000< of 0.05 which means there is an influence between verbal bullying and interpersonal intelligence. Also the value of the rhitung is 0.975 further compared to the rtable with N=18 which is listed at the significance level of 5%= 0.468. From the result it appears that the ritung is greater than the rtabel or can be represented at a significance rate of 5% (0.975 > 0.297). It means "there is a significant relationship between verbal bullying and interpersonal intelligence of high school students of SD Inpres Karuwisi 1 Makassar". This is determined by the correlation calculation of 0.975. So it can be concluded that the higher the verbal bullying then the lower the interpersonal intelligence of the student, on the other hand the lower verbal Bullying the higher interpersonal intelligence the student.